Progression of liver fibrosis in blood donors infected with hepatitis C virus - Silva, Giovanni Faria [UNESP]; Coelho, Kunie Iabuki Rabello [UNESP]; Nishimura, Nancy F.; Soares, Elza Cotrim (My University, 2004)
Background/Aims. Chronic hepatitis by HCV is progressive towards cirrhosis, with variable rate. We evaluated the rate of fibrosis progression (RFP), risk factors associated with advanced fibrosis (F3 and F4), and estimated the evolution time to cirrhosis. Methods. We transversely selected 142 blood donors infected only with HCV, with a known route of infection, submitted to liver biopsy at admission. RFP= ratio between stage of fibrosis (METAVIR)/estimated duration of infection in years. Non-parametric tests and logistic regression analysis, with significance level of 5% were used. Results. Median RFP was 0.086 U/year (0.05 - 0.142). Ten patients had F4 and 25 had F3. Median RFP values were significantly different (p=0.001) from one age group at contamination to the others and ALT and AST levels. There were no differences in the expected evolution to cirrhosis between intermediate fibrosers (F2) and the rapid fibrosers (F3 and F4). The independent variables associated with advanced fibrosis were ALT (OR 7.2) and GGT (OR 6.4) and age at inclusion (OR 1.12). Conclusion. This study suggests that RFP is extremely variable, it is exponential with age, and mainly influenced by host characteristics, especially age at contamination and possibly ethnical group. These asymptomatic patients had high percentage of fibrosis F2, F3 and F4.
Keywords: Chronic hepatitis C; Fibrosis progression; Risk factors; alanine aminotransferase; alcohol; aspartate aminotransferase; gamma glutamyltransferase; virus RNA; adult; age; alcohol consumption; blood donor; blood transfusion; controlled study; disease course; disease duration; ethnic group; female; hepatitis C; Hepatitis C virus; histopathology; human; intravenous drug abuse; liver biopsy; liver fibrosis; logistic regression analysis; major clinical study; male; nonparametric test; risk factor; viral contamination; Adult; Blood Donors; Disease Progression; Female; Hepatitis C, Chronic; Humans; Liver Cirrhosis; Logistic Models; Male; Middle Aged; Multivariate Analysis; Risk Factors; Statistics, Nonparametric